2006
DOI: 10.1677/joe.1.06808
|View full text |Cite
|
Sign up to set email alerts
|

Gastric estrogen directly induces ghrelin expression and production in the rat stomach

Abstract: Ghrelin, an endogenous ligand for the GH secretagogue receptor, is predominantly produced in the stomach. Little is known about the regulation mechanism of gastric ghrelin. Here, we report that estrogen synthesized in the stomach induces rat gastric ghrelin gene expression and production. We established a gastric ghrelin cell enrichment method using Percoll centrifugation and then studied the effect of estrogen and/or its antagonist on ghrelin expression and production. Treatment with estrogen for 8 h signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 43 publications
4
39
1
3
Order By: Relevance
“…Ghrelin, an endogenous ligand for the growth hormone secretagogue receptor, is predominantly produced in the stomach (25), and its expression and release are thought to be regulated by gastric estrogen in a paracrine fashion (26). Recently, ghrelin levels have been observed to be upregulated in a chronic stress model in rats (27), which was originally developed by our group as a comprehensive fatigue model (21).…”
Section: Pet Studies In Fatigued Ratsmentioning
confidence: 99%
“…Ghrelin, an endogenous ligand for the growth hormone secretagogue receptor, is predominantly produced in the stomach (25), and its expression and release are thought to be regulated by gastric estrogen in a paracrine fashion (26). Recently, ghrelin levels have been observed to be upregulated in a chronic stress model in rats (27), which was originally developed by our group as a comprehensive fatigue model (21).…”
Section: Pet Studies In Fatigued Ratsmentioning
confidence: 99%
“…In that study, we found that estrogen treatment significantly stimulated ghrelin mRNA expression ( Figure 3A) and production in a dose-dependent manner and that treatment of minced stomach tissue with formestane, an aromatase inhibitor, decreased ghrelin expression level [23] . Given that a significant increase in estrogen concentration in the portal vein compared with that in the artery was observed in intact rats, but not in gastrectomized rats [22] , the concentration of gastric estrogen must be higher than that of plasma estrogen.…”
Section: Regulatory Role Of Gastric Estrogenmentioning
confidence: 77%
“…Therefore, in a previous study, using isolated stomach cells, which are rich in ghrelin cells, we determined the direct effect of estrogen on stomach ghrelin expression and production [23] . In that study, we found that estrogen treatment significantly stimulated ghrelin mRNA expression ( Figure 3A) and production in a dose-dependent manner and that treatment of minced stomach tissue with formestane, an aromatase inhibitor, decreased ghrelin expression level [23] .…”
Section: Regulatory Role Of Gastric Estrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, ovariectomy or orchiectomy in female and Page 21 of 41 A c c e p t e d M a n u s c r i p t 21 male adult rats, respectively, did not affect gastric ghrelin mRNA expression (Gualillo et al, 2001). By contrast, others found that estradiol produced locally in the stomach was able to stimulate ghrelin gene expression even after gonadectomy (Sakata et al, 2006). Another study reported suppressive effects of ovarian estradiol on stomach ghrelin gene expression as well as on the plasma ghrelin concentration (Matsubara et al, 2004).…”
Section: Ghrelin and The Polycystic Ovary Syndromementioning
confidence: 97%